2021
DOI: 10.3389/fcvm.2021.706999
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of Metabolic Syndrome Alter the Risks of Cardiovascular Diseases and All-Cause Mortality: Evidence From a Prospective Cohort Study

Abstract: Background: Metabolic syndrome (MetS) at baseline increases the risks of cardiovascular diseases (CVD) and all-cause mortality. However, MetS status is changeable during follow-up. The associations of dynamic changes of MetS with CVD and all-cause mortality remain unclear.Methods: Thirty-one thousand four hundred eighty-one eligible subjects were included from the Kailuan cohort. Dynamic changes of MetS were divided into four patterns as MetS-free, MetS-developed, MetS-recovery and MetS-stable. The outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
3
11
0
1
Order By: Relevance
“…With the global epidemic of obesity and diabetes, the incidence of metabolic disorders has skyrocketed, which will bring huge social and economic burdens ( Miranda et al., 2005 ). Metabolic syndrome (MetS), also known as insulin resistance syndrome, refers to a cluster of physical risk factors (including abdominal obesity; elevated triglycerides, fasting glucose, and blood pressure; and reduced high-density lipoprotein cholesterol) that are associated with increased risks of cardiovascular disease ( Broekhuizen et al, 2011 ; Zomer et al, 2014 ; Khalil et al, 2018 ), T2D ( Wannamethee et al., 2005 ; Rohm et al., 2022 ) and even mortality ( Kassi et al., 2011 ; He et al, 2021 ). Accumulating evidence has recognized MetS to be a systemic proinflammatory state with gut flora dysbiosis and adipose inflammation as putative pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…With the global epidemic of obesity and diabetes, the incidence of metabolic disorders has skyrocketed, which will bring huge social and economic burdens ( Miranda et al., 2005 ). Metabolic syndrome (MetS), also known as insulin resistance syndrome, refers to a cluster of physical risk factors (including abdominal obesity; elevated triglycerides, fasting glucose, and blood pressure; and reduced high-density lipoprotein cholesterol) that are associated with increased risks of cardiovascular disease ( Broekhuizen et al, 2011 ; Zomer et al, 2014 ; Khalil et al, 2018 ), T2D ( Wannamethee et al., 2005 ; Rohm et al., 2022 ) and even mortality ( Kassi et al., 2011 ; He et al, 2021 ). Accumulating evidence has recognized MetS to be a systemic proinflammatory state with gut flora dysbiosis and adipose inflammation as putative pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The development of IFG and borderline high LDL-C from normality was associated with non-significantly higher risks of CVD and its subtypes than long-term normal concentrations (HR: 1.26, 95% CI: 0.98-1.61), perhaps because of insufficient sample size, but implying that these abnormalities may cause significant harm. Similarly, He et al (45) found that differing patterns of changes in metabolic parameters were associated with different risks of CVD. The effects of particular risk factors on CVD depend on the intensity and duration of exposure (46), and because serum FBG and LDL-C concentrations tend to increase with age (47), the risk of CVD would be expected to be higher in individuals with IFG and borderline high LDL-C. We also found no increase in the risk of CVD in those participants who had at least one abnormality at baseline, but none subsequently (HR: 1.00, 95% CI: 0.82-1.20).…”
Section: Discussionmentioning
confidence: 92%
“…Швец и соавт., в котором наибольший вклад в риск летального исхода внесли инсульт в анамнезе и 3-я стадия ХБП наряду с возрастом, перенесённым ранее инфарктом миокарда и отсутствием ЧКВ [7]. Наши результаты подтвердили данные литературы о том, что сахарный диабет -фактор, увеличивающий смертность от сердечно-сосудистых заболеваний, несмотря на своевременную реваскуляризацию и оптимальную терапию [8]. Артериальную гипертензию регистрировали в 89% случаев, что соответствует средним показателям в других регистрах [1,5].…”
Section: Discussionunclassified